Traditional Chinese Medicine Recorded by Missionaries (1887—1932): A Study Centered on The China Medical Missionary Journal - Yanran LI; Na YAN; Jin LU (Chinese Medicine and Culture)
Abstract. It was in The China Medical Missionary Journal (《博医会报》, CMMJ), first published in Shanghai in 1887, that traditional Chinese medicine (TCM) made its academic debut on the international stage. It integrated medical evangelism, hospital reports and world medical development at its beginning, and it was transformed into a purely academic journal in 1907. There are many records related to TCM in it, such as TCM diagnosis, treatment methods and clinical practices. These records show the process of how the missionaries observed, understood, learned, and used TCM. They also reflect the attitudes of medical missionaries towards TCM after experiencing it in its homeland, China at that time. The writings of missionaries on TCM represent a confluence of Eastern and Western medical research and cultural interactions, contributing significantly to the study of modern Chinese medical advancements and Sino-Western cultural exchanges.